Assessing Success Factors Of Web-Based Disaster Information Systems That Influence Individual Disaster Preparedness - Mortazavi Rashtchi, Sara (2011)
This study examines the role of Disaster Management System for disaster preparedness by applying information system. In order to design successful information systems for disaster management, a context related understanding of the success factors for achieving effective disaster management information system is necessary. Accordingly, the goal of this research is to identify the success measures of effective web-based disaster management information system according to the DeLone & McLean\'s IS success model that influence individual preparedness.